Feasibility of Quality Improvement of Jute Seed by Plant Extracts (Progressive Agriculture, 2013)
Five plant extracts viz. garlic tablet, allamanda tablet, neem leaf extract, bishkatali leaf extract and zinger rhizome extract were assessed as seed treating agents against seed-borne pathogens of jute. Farmers seeds carry seed-borne fungi and their prevalence varies in varieties and locations. Garlic tablet was effective in controlling seed-borne fungal infection; consequently the seed germination was high. The effect of allamanda tablet was similar to that of garlic tablet. Neem leaf extract was able to reduce seed-borne fungi but the other three extracts were not effective in controlling seed-borne infection. The performance of garlic tablet was similar to that of Vitavax-200. A significant increase in seedling vigor was also observed over untreated control after garlic treatment.DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16461 Progress. Agric. 22(1 & 2): 1 10, 2011